(untitled) (MAUSAM, 2003)
Dry farming regions (DFRs) in India often witness incidences of drought. In the present study decile method has been applied to six stations viz. Delhi, Jaipur, Ahmedabad, Jalgaon, Ahmednagar and Anantapur. For this purpose weekly rainfall data for 80 years (1901-80) have been used, for the kharif period i.e. rainy crop growing season extending from June to early October. Three decile ranges i.e. 3rd, 5th and 7th have been used to identify agricultural, meteorological and hydrological droughts. The commencement of sowing operations and duration of agricultural season have also been determined and discussed. The decile approach, it is suggested, enables progressive update of the probability of occurrence of rains during the crop growing season. This can be achieved by adding, weekly rainfall separately to the above deciles or three probability levels for remaining part of season. It gives sets of estimates of rainfall during the growing season. The methodology was applied on the independent data set of rainfall for the years 1981-96. The types of droughts have been clearly identified. Most vulnerable areas of agricultural drought (like Anantapur) could be identified.